Physical and gamma-ray shielding characteristics of Copper Matrix Refractory High Entropy Alloy Reinforced Composite: an extensive experimental and computational approach - Kuluozturk, Zehra Nur; Kuluozturk, Muhammed Fatih; Guler, Seval Hale; Dogru, Mahmut; Guler, Omer (Pergamon-Elsevier Science Ltd, 2026)
Refractory High Entropy Alloys (RHEAs) have become an attractive alternative for radiation shielding applications due to their high mechanical strength, thermal resistance, structural stability, and compositional diversity. In this study, Cu-based composites containing 0-20 wt% RHEAs were prepared, and the crystal structure, morphological properties, and radiation shielding performance of the synthesized Cu-RHEA were investigated experimentally and theoretically. Measurements were performed using a NaI(Tl) detector system with point sources of 133Ba, 137Cs, 22Na and 60Co emitting gamma energies in the range of 0.356-1.333 MeV. In addition, theoretical calculations were carried out using the FLUKA and Phy-X/PSD, showing good agreement with the experimental data. Linear attenuation coefficient (LAC) values were found to decrease with increasing photon energy and to increase with increasing RHEA content. In the 0.356-1.333 MeV energy range, the experimental LAC values ranged from 0.7599 to 0.3818 cm- 1 for Cu-RHEA0 and from 0.9594 to 0.4221 cm- 1 for Cu-RHEA20. At 0.662 MeV, the LAC value increased from 0.5426 cm- 1 for Cu-RHEA0 to 0.6183 cm-1 for Cu-RHEA20. In terms of half-value layer (HVL), the Cu-RHEA20 sample exhibited a value of 0.729 cm at 0.356 MeV, approximately 20% lower than the 0.912 cm value of Cu-RHEA0. Compared with conventional shielding materials reported in the literature, the Cu-RHEA20 sample reached a maximum mass attenuation coefficient (MAC) of 76.279 cm2 & sdot;g- 1 at 0.015 MeV, demonstrating clear superiority over ordinary concrete with a value of 7.079 cm2 & sdot;g- 1. These findings demonstrate that increasing RHEA content improves gamma-ray attenuation performance, highlighting Cu-RHEA20 as a promising next-generation shielding material.
Keywords: Refractory High Entropy Alloy (Rhea); Gamma Shielding; Gamma Spectroscopy System; Fluka